2012
DOI: 10.3109/03630269.2012.749490
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum ofα-Thalassemia Mutations in the Kurdish Population of Northeastern Iraq

Abstract: In an attempt to determine the spectrum of α-thalassemia (α-thal) mutations in the Kurdish population of Northeastern (NE) Iraq, a total of 101 unrelated adults with unexplained hypochromia and/or microcytosis were enrolled. α-Thalasssemia mutations were characterized by gap polymerase chain reaction (gap-PCR), multiplex PCR (m-PCR) and reverse hybridization and sequencing for both α genes. A total of nine α-thal mutations were characterized including four deletional ones: -α(3.7) (rightward), - -(MED-I), -(α)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
5
6
0
Order By: Relevance
“…In the current study, we have identified eight different α-globin gene mutations, four of which are deletion mutations (--MED , -α 3.7 , -α 4.2 , and -(α) 20.5 ) and the remaining four are non-deletion mutations (α2 poly-A1, Hb Adana, α2 IVS1 (-5nt), and α2 poly-A2). Comparable to the results of earlier reports by Al-Allawi et al [20,21], we found the spectrum of α-globin gene defects restricted to a relatively limited number of mutations. However, this finding is unlike to what have been observed in Iran, Turkey, Sardinia, and Cyprus, where the mutations are more heterogeneous [23,24].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the current study, we have identified eight different α-globin gene mutations, four of which are deletion mutations (--MED , -α 3.7 , -α 4.2 , and -(α) 20.5 ) and the remaining four are non-deletion mutations (α2 poly-A1, Hb Adana, α2 IVS1 (-5nt), and α2 poly-A2). Comparable to the results of earlier reports by Al-Allawi et al [20,21], we found the spectrum of α-globin gene defects restricted to a relatively limited number of mutations. However, this finding is unlike to what have been observed in Iran, Turkey, Sardinia, and Cyprus, where the mutations are more heterogeneous [23,24].…”
Section: Discussionsupporting
confidence: 77%
“…The carrier rate of α-thalassaemia in Iraq is estimated at < 1%, but no study has yet rectified the exact carrier rate in this region. So far, a couple of small studies by Al-Allawi et al have described the spectrum of α-globin gene mutations among carriers in the neighboring provinces of Dohuk and Sulaimaniyah [20,21]. The current study is the first to tackle a relatively large cohort of patients with HbH disease, characterized their genotypes, and correlated genotypes to patients' clinical phenotypes.…”
Section: Discussionmentioning
confidence: 82%
“…The polyA2 mutation was documented in 2.0% of our alpha thalassemic alleles. This has been described in Iraq: 1%; Turkey: 4%; Iran: 0.5% and was not detected in Israel, Jordan, UAE, Saudi Arabia, Algeria, and Oman (Table ). Anti‐3.7 triplication, a sporadic mutation, without any hematological sign unless associated with beta globin mutation was detected in only one of our patients, with an allele frequency of 1% which is similar to the Iranian population of the Kerman province (26%) and lower than that reported in Israel (3.2%) .…”
Section: Discussionmentioning
confidence: 78%
“…--MED mutation seems to be specific to Mediterranean areas. It has been reported among the first three or four most frequent mutations in Mediterranean and Middle Eastern populations whereas it has not to been seen in Far Eastern populations [7,16,17,19,20,24,26].…”
Section: Resultsmentioning
confidence: 92%